A World Atlas of Translation - Gambier, Yves (Benjamins Translation Library, 2019)
Intro -- A World Atlas of Translation -- Editorial page -- Title page -- Copyright page -- Table of contents -- Preface -- Six consultants -- Identifying traditions -- Looking for translation -- A World Atlas of Translation -- Going through the steps -- References -- Chapter 1. Translating in the Pacific: Rendering the Christian Bible in the islanders' tongues -- 1. Scope and terminology -- 2. Current linguistic landscape -- 3. How to say "Translate" in Pacific languages -- 4. Early linguistic interactions and translation activities -- 5. New focus of translation activities - the Christian Bible -- 6. Recapitulation of a century (1818-1918) of Bible translation activities -- 7. Translating the Christian Bible in the Pacific from 1918 to date -- 8. Linguistic challenges faced by Pacific translators -- 9. Conclusion: Looking forward to the future -- References -- Chapter 2. Recent tradition in Australia -- 1. Preamble -- 2. Overview -- 3. The development of the concept of Translation -- 4. Formalising translation -- 5. Accreditation and training -- 6. Translation in practice -- 7. What is the concept of Translation in Australia? -- 8. A notion of Translation? -- References -- Chapter 3. Japanese conceptualizations of 'translation' -- 1. Introduction -- 2. The impact of script: Translation as transposition and gloss reading -- 3. Languages as fluid entities -- 4. Introduction of European concepts of Translation -- 5. The premodern professional norm with Dutch -- 6. Translation as scholarly mining and interpretation -- 7. Vernacular renditions of Chinese works -- 8. Intralingual translations -- 9. Inter-register translations -- 10. Imitation as creativity -- 11. Micro-level amalgams -- 12. Translation as a two-stage process -- 13. Moving 'mainstream' -- 14. Collaborative and surrogate translating and translator (in)visibility